2018
DOI: 10.1038/s41598-018-34376-w
|View full text |Cite
|
Sign up to set email alerts
|

Heat-induced Bone Diagenesis Probed by Vibrational Spectroscopy

Abstract: Complementary vibrational spectroscopic techniques – infrared, Raman and inelastic neutron scattering (INS) – were applied to the study of human bone burned under controlled conditions (400 to 1000 °C). This is an innovative way of tackling bone diagenesis upon burning, aiming at a quantitative evaluation of heat-induced dimensional changes allowing a reliable estimation of pre-burning skeletal dimensions. INS results allowed the concomitant observation of the hydroxyl libration (OHlibration), hydroxyl stretch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
76
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(93 citation statements)
references
References 56 publications
(64 reference statements)
13
76
2
2
Order By: Relevance
“…These characteristics are observed when the materials are fired. Comparison to the data obtained in the previous studies showed that the Raman spectroscopy confirmed that this spectrum was similar to that of the artificially produced [Ca 2 (PO 4 ) 2 ], bones containing collagen, and materials taken from burned animal bones(Figure 7)(Bordes et al, 2017;Marques et al, 2018;Jillavenkatesa and Condrate Sr, 1998).Natural white materials with Ca and P as the main elements, include fluorapatite[Ca 5 (PO 4 ) 3 F 2 ], which is a major component of teeth and bones. Fluorapatite mostly comes from Canada, Mexico, Brazil, Russia, Japan, and Myanmar, and is not produced in Korea(Doopedia, 2020).…”
supporting
confidence: 74%
“…These characteristics are observed when the materials are fired. Comparison to the data obtained in the previous studies showed that the Raman spectroscopy confirmed that this spectrum was similar to that of the artificially produced [Ca 2 (PO 4 ) 2 ], bones containing collagen, and materials taken from burned animal bones(Figure 7)(Bordes et al, 2017;Marques et al, 2018;Jillavenkatesa and Condrate Sr, 1998).Natural white materials with Ca and P as the main elements, include fluorapatite[Ca 5 (PO 4 ) 3 F 2 ], which is a major component of teeth and bones. Fluorapatite mostly comes from Canada, Mexico, Brazil, Russia, Japan, and Myanmar, and is not produced in Korea(Doopedia, 2020).…”
supporting
confidence: 74%
“…This behavior was observed for all samples under study, in accordance with previous results obtained from INS and FTIR spectroscopy. 5,6,21,51 Fig . 2 represents the renements of the neutron diffraction data measured for tibia sections (T42) burned at high temperatures (800, 900 and 1000 C).…”
Section: Resultsmentioning
confidence: 99%
“…13,22,[34][35][36][37][38] Following several successful studies in burned human bone (400 to 1000 C) by combined FTIR, Raman and INS. [4][5][6]8,21,26 The present study aimed to complement these spectroscopic results with diffraction data leading to a more detailed interpretation of the chemical and microcrystallinity variations already revealed spectroscopically, that will identify skeletal remains subject to unknown heating conditions. Bone's chemical and crystallinity changes were probed, upon an aerobic burning process at different maximum temperatures (from 400 to 1000 C, chosen according to those reached in re and explosion settings).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations